Clinical features and prognostic indicators in upper-tract urothelial carcinoma with bone metastasis - Zhou, Mingping; Zhang, Jianxin; Chen, Xiaowei; Wang, Zhan; Liang, Wei (Frontiers in Surgery, 2022)
Purpose: With the gradual increase in the incidence of upper-tract urothelial carcinoma (UTUC), its metastatic disease has attracted much attention. The prognosis of UTUC patients with bone metastasis is worse than that of UTUC patients with other metastases. Therefore, the current study is performed to analyze the clinicopathologic features and survival predictors among UTUC patients with bone metastasis. Patients and Methods: We reviewed the Surveillance, Epidemiology, and End Results (SEER) database to select cases diagnosed with UTUC and bone metastasis at present from 2010 to 2016. Overall survival (OS) and cancer-specific survival (CSS) were first performed by applying univariate Cox regression analysis. Then we performed multivariate Cox analysis to determine independent predictors of survival. Forest plots were drawn by GraphPad 8.0.1 and used to visually display the results of multivariate analysis. Kaplan-Meier method was applied to intuitively show the prognosis difference of each independent risk factor. Results: We finally identified 380 UTUC patients with bone metastasis for survival analysis, of which 230 males (60.5%) and 150 females (39.5%). The mean and median age at diagnosis were 71 and 72 years, respectively. Simultaneous lung metastasis (33.4%) and liver metastasis (31.1%) were more common in UTUC patients with bone metastasis. The 1-year OS and CSS rates of this research population were 23.8% and 26.6%, respectively. Multivariate Cox proportional hazards modeling controlling for surgery, chemotherapy, brain metastasis, liver metastasis, lung metastasis, and marital status, revealed that surgery, chemotherapy, no liver metastasis, no lung metastasis, and married status predicted for better OS and CSS. Conclusion: Surgery and chemotherapy are optimal management of UTUC patients with bone metastasis. Active treatments on lung and liver metastases should be performed. The prognosis of patients with unmarried status or others should be further improved.